PREREQUISITES AND AGGREGATIVE MANAGEMENT TECHNOLOGY OF INNOVATIVE RECEPTIVITY OF INDUSTRIAL ENTERPRISES - E. M. Karpenko; S. Yu. Komkov (Наука и техника)
The paper is devoted to the problems conceming development of integrated management technology of innovative receptivity of industrial enterprises. The work highlights and substantiates initial prerequisites pertaining to management of the innovative receptivity of enterprises; description of the proposed aggregative management technology is presented in .le paper. The paper gives results of evaluating level and importance of various forms of innovative receptivity of six industrial enterprises of Gomel province. The work contains a conclusion about the necessity of system optimization in respect of innovative receptivity of tfie analyzed enterprises at the expense of coordinated correction of its intemal and extemal factors. The main results of practical approbation of the suggested management technology of the innovative receptivity are shown in the paper. The paper points out main directions of optimization regarding innovative receptivity of the analyzed enterprises at strategic and tactical levels of managing the given characteristic.